ANTIOXIDANT ACTIVITY TEST OF Acacia sp. BARK EXTRACT - Taufiq Rinda Alkas (PROSIDING SEMINAR KIMIA, 2015)
Acacia sp. bark was extracted by using Soxhlet Extractor with acetone : water solvents (4 : 6) for 2 hours, extraction with n-hexane, added by NaCl solution, then hydrolized with aqueous hydrochloric acid and finally the precipitate is recrystalized.The antioxidant activity tests were used in this research: Thiocyanate method and Thiobarbituric acid (TBA) method. Thiocyanate method is done for 10 days and the sample absorbance is measured with UV-Vis Spectrophotometre at λ = 500 nm. The TBA method is done with sample absorbance measurement at λ = 532 nm tor 10 days. In this condition, the sample consisted of the mixture of oleic acid 0,05% in absolute ethanol, phosphate buffer in pH=7 with the extract variation (0,05% and 0,09%), BHT and control. The result showed a positive indication that the extract can be used as a natural antioxidant. This research showed higher concentration of the extract also made higher antioxidant activity.